Effect of Ethanol Extract of Cherry (Muntingia calabura L.) Leaves on the Estrous Cycle in Female Mice (Mus musculus) - Maulidatuz Zahro; Harlita Harlita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Cherry (Muntingia calabura L.) leaves contain primary secondary metabolites in the form of flavonoids that have the potential to inhibit fertility by interfering with ovarian, uterus, or vaginal function. One of the parameters that can be used to assess the antifertility potential of a compound or herbal extract is the estrous cycle. This study aimed to determine the effect of cherry leaves ethanol extract intake on the estrous cycle in female mice (Mus musculus). This study used a Complete Random Design (CRD) with 3 treatments, namely control of Na CMC 1% (C), cherry leaves extract at a dose of 125 mg/kg of mice body weight (T1), and 250 mg/kg of mice body weight (T2), each with 3 replicates. The results showed that cherry leaves ethanol extract did not have a significant effect on the length of the estrous cycle of mice analyzed by the Kruskal–Wallis test (Asymp value. Sig > 0.05), although there is a tendency for the estrous cycle in the treatment group to be longer than the control group. This study provides insights for follow-up research with more diverse doses, treatment duration, and reproductive parameters in determining the antifertility activity of an herbal metabolite compound.